Identification of an interleukin (IL)-25–dependent cell population that provides IL-4, IL-5, and IL-13 at the onset of helminth expulsion - Fallon, Padraic G. (The Rockefeller University Press, 2006)
Type 2 immunity, which involves coordinated regulation of innate and adaptive immune responses, can protect against helminth parasite infection, but may lead to allergy and asthma after inappropriate activation. We demonstrate that il25(−/−) mice display inefficient Nippostrongylus brasiliensis expulsion and delayed cytokine production by T helper 2 cells. We further establish a key role for interleukin (IL)-25 in regulating a novel population of IL-4–, IL-5–, IL-13–producing non–B/non–T (NBNT), c-kit(+), FcɛR1(−) cells during helminth infection. A deficit in this population in il25(−/−) mice correlates with inefficient N. brasiliensis expulsion. In contrast, administration of recombinant IL-25 in vivo induces the appearance of NBNT, c-kit(+), FcɛR1(−) cells and leads to rapid worm expulsion that is T and B cell independent, but type 2 cytokine dependent. We demonstrate that these IL-25–regulated cells appear rapidly in the draining lymph nodes, implicating them as a source of type 2 cytokines during initiation of worm expulsion.